Gold Nanoparticles Permit In Situ Absorbed Dose Evaluation in Boron Neutron Capture Therapy for Malignant Tumors - Alexander Zaboronok; Sergey Taskaev; Olga Volkova; Ludmila Mechetina; Anna Kasatova; Tatiana Sycheva; Kei Nakai; Dmitrii Kasatov; Aleksandr Makarov; Iaroslav Kolesnikov; Ivan Shchudlo; Timofey Bykov; et al. (MDPI AG, 2021)
Boron neutron capture therapy (BNCT) is an anticancer modality realized through 10B accumulation in tumor cells, neutron irradiation of the tumor, and decay of boron atoms with the release of alpha-particles and lithium nuclei that damage tumor cell DNA. As high-LET particle release takes place inside tumor cells absorbed dose calculations are difficult, since no essential extracellular energy is emitted. We placed gold nanoparticles inside tumor cells saturated with boron to more accurately measure the absorbed dose. T98G cells accumulated ~50 nm gold nanoparticles (AuNPs, 50 µg gold/mL) and boron-phenylalanine (BPA, 10, 20, 40 µg boron-10/mL), and were irradiated with a neutron flux of 3 × 108 cm−2s−1. Gamma-rays (411 keV) emitted by AuNPs in the cells were measured by a spectrometer and the absorbed dose was calculated using the formula D = (k × N × n)/m, where D was the absorbed dose (GyE), k-depth-related irradiation coefficient, N-number of activated gold atoms, n-boron concentration (ppm), and m-the mass of gold (g). Cell survival curves were fit to the linear-quadratic (LQ) model. We found no influence from the presence of the AuNPs on BNCT efficiency. Our approach will lead to further development of combined boron and high-Z element-containing compounds, and to further adaptation of isotope scanning for BNCT dosimetry.